Micromycetes on highbush blueberry Vaccinium corymbosum L. leaves - Joanna Kwiatkowska (Acta Mycologica, 2023)
The study aimed at the identification of micromycetes found on the leaves of highbush blueberries Vaccinium corymbosum . The study yielded 23 fungal species (261 colonies) isolated from living and fallen leaves with symptoms of disease (necrosis and spots). The dominant species were Pestalotiopsis sydowiana , Alternaria alternata , Epicoccum nigrum , Trichoderma viride , T. harzianum , Pestalotia spp., Penicillium expansum , P. jensenii , Mortierella spp., Truncatella spp., and Dichotomopilus spp.